Increased adherence eight months after switch from twice daily calcineurin inhibitor based treatment to once daily modified released tacrolimus in heart transplantation - Doesch AO; Mueller S; Akyol C; Erbel C; Frankenstein L; Ruhparwar A; Ehlermann P; Dengler TJ; Katus HA (Dove Medical Press, 2013)
Andreas O Doesch,1 Susanne Mueller,1 Ceylan Akyol,1 Christian Erbel,1 Lutz Frankenstein,1 Arjang Ruhparwar,2 Philipp Ehlermann,1 Thomas J Dengler,3 Hugo A Katus11Department of Cardiology, University of Heidelberg, Heidelberg, Germany; 2Department of Cardiovascular Surgery, University of Heidelberg, Heidelberg, Germany; 3Department of Cardiology, SLK-Kliniken Heilbronn, Bad Friedrichshall, GermanyBackground: Modified-release tacrolimus (TAC) is a new, once-daily oral formulation of the established immunosuppressive agent TAC. This study evaluated long-term patient adherence, as well as safety and efficacy, in stable patients after heart transplantation (HTx) who switched from a conventional twice daily calcineurin inhibitor-based regimen (TAC or cyclosporine A [CsA]) to a once-daily modified-release TAC regimen.Methods: Stable patients were switched from conventional TAC or CsA (twice-daily dosing) to modified-release TAC (once-daily dosing) according to manufacturer's recommendations using a pre-experimental design. Self-reported adherence was assessed at baseline and 8 months after the switch with the Basel Assessment of Adherence with Immunosuppressive Medication Scale (BAASIS). Additionally, routine laboratory values were analyzed 8 months after switch.Results: Of 76 patients (58 male, 18 female) initially included, 72 were available for statistical analysis, as modified-release TAC was discontinued due to diarrhea in one patient and gastrointestinal discomfort in three patients. Overall nonadherence at baseline for any of the four BAASIS items was 75.0% versus 40.3% after 8 months (P<0.0001). After 8 months, adherence was improved in 41 patients (56.9%), unchanged in 27 (37.5%), and reduced in four patients (5.6%). The BAASIS visual analog scale score improved significantly from 87.0% ± 13.5% to 97.5% ± 5.7% (P<0.0001). No significant changes were observed for hematological, renal, or liver function parameters after 8 months (all P=not significant).Conclusion: To our knowledge, this is the first study in stable patients after HTx to demonstrate a significant improvement in long-term (ie, 8-month) patient adherence after the switch to modified-release TAC. Modified-release TAC was generally well tolerated. Further studies are currently underway to investigate long-term safety after HTx of various calcineurin inhibitors for prevention of rejection and occurrence of side effects.Keywords: heart transplant, immunosuppression, modified-release tacrolimus, long-term adherence